Standardization of juice concentration for preparation of phalsa nectar and changes during storage (IASH Indian Journal of Arid Horticulture, 2024)
The experiment on preparation of phalsa nectar was conducted at Regional Research Station, Bawal. The ripe fruit of phalsa were harvested, sorted and blended with 0.5 litre water per kilogram fruit. It was heated to 70ºC and filtered to extract juice. The required amount of juice, sugar and citric acid were added to fix the concentration of juice (20.0, 22.5 and 25.0 %), TSS (15ºB) and titratable acidity (0.3%). After preparation of nectar, it was pasteurized and stored for 90 days to study the changes during storage. The TSS of the nectar increased up to 30 days of storage later on it decreased significantly. Titratable acidity and ascorbic acid content in nectar decreased with increase in storage period. However, sensory rating increased up to 60 days of storage and thereafter it was at par with 60 days of storage. Ascorbic acid content increased with increase in juice concentrations in nectar. Ascorbic acid content in all the concentrations of juice decreased with the increase in storage period. However, sensory rating decreased at 25% juice concentrations in the nectar. Overall, the phalsa nectar was rated as “moderately liked” or better by consumers and remained acceptable for up to 90 days of storage.